1993
DOI: 10.1016/0092-8674(93)90256-p
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomal organization of telomere-specific chromatin in rat

Abstract: Rat liver interphase chromosomes have telomeres 20-100 kb in length. Micrococcal nuclease digestion of nuclei cleaves telomeres with a uniform 157 bp periodicity, producing soluble particles that sediment in sucrose gradients exactly like oligonucleosomes. The monomeric telomere particles comigrate with nucleosome core particles on nucleoprotein and DNA gels but do not bind H1. DNAase I cleaves telomere nucleoprotein into a series of bands spaced by about 10.4 bp and with the same intensity distribution as ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
2
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(150 citation statements)
references
References 66 publications
6
140
2
2
Order By: Relevance
“…Because of its remarkable regenerative capacity the rat liver has proven to be an excellent model for studies of cell proliferation and carcinogenesis (Cayama et al, 1978;Kaufmann et al, 1981). In spite of an extensive literature on hepatocarcinogenesis, there are few reports on telomeres and telomerase activity in normal rat liver and liver tumors (Makarov et al, 1993;Yoshimi et al, 1996). To determine whether altered expression of telomerase might play a role in rat hepatocarcinogenesis, we characterized telomerase activity in quiescent and regenerating liver, isolated hepatocytes, cultured hepatic epithelial stem-like cells from normal liver, and in immortal and tumorigenic derivatives of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its remarkable regenerative capacity the rat liver has proven to be an excellent model for studies of cell proliferation and carcinogenesis (Cayama et al, 1978;Kaufmann et al, 1981). In spite of an extensive literature on hepatocarcinogenesis, there are few reports on telomeres and telomerase activity in normal rat liver and liver tumors (Makarov et al, 1993;Yoshimi et al, 1996). To determine whether altered expression of telomerase might play a role in rat hepatocarcinogenesis, we characterized telomerase activity in quiescent and regenerating liver, isolated hepatocytes, cultured hepatic epithelial stem-like cells from normal liver, and in immortal and tumorigenic derivatives of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of rat telomeres has suggested that mammalian telomeres are packaged in normal nucleosomal arrays (39). How 16 h to remove all traces of formaldehyde.…”
mentioning
confidence: 99%
“…In contrast with yeast telomeres, which lack histones (Wright et al, 1992), mammalian telomeres are nucleosomal (Makarov et al, 1993;Lejnine et al, 1995) and their chromatin is enriched with repressive histone marks, including H3K9me3 and H4K20me3 (me3 represents trimethylation), and the heterochromatinspecific factors chromobox homolog (CBX) 1, 3 and 5 (García-Cao et al, 2004;Gonzalo et al, 2006). Depletion of these heterochromatic marks correlates with remarkable elongation of telomeres (Marión and Blasco, 2010;Marión et al, 2011;Varela et al, 2011).…”
Section: Telomere Length Regulationmentioning
confidence: 99%